Social conflict in the contemporary French roman noir - Kimyongür, Angela (Australian journal of crime fiction, 2025)
Conflict is by definition at the heart of the crime novel: most evidently in the usually violent conflict between victim and perpetrator but also in a more abstract, though equally important, way in the conflict between the perpetrator and the social order that s/he has transgressed. The classic detective story that Tzvetan Todorov classifies as the “whodunit” in his typology of detective fiction (1977, p. 43), in which the mystery of a crime, usually a murder, and the circumstances leading up to it are investigated and resolved by an authoritative detective figure, is one in which the criminal is the enemy of a social order, often that of bourgeois or upper-class society, that he or she has disrupted. Contemporary French crime writer Dominique Manotti (2009) opposes the essentially reassuring nature of the roman policier—similar in its structure to Todorov’s ‘whodunit’—as a form which is “by definition a novel of order”, to the roman noir she espouses. The roman noir, akin to Todorov’s “thriller” (1977, p. 47) offers little reassurance. In this type of fiction, the disorder engendered by criminal acts, symptomatic as they are of a permanently disordered society, is dispelled only to return.
Keywords: Social conflict; French roman noir